A Simulator for Micro Programming and Hardware Simulation Integrated in a Computer Hardware Project: محاكي للبرمجة المصغرة ومحاكاة الأجهزة المدمج في مشروع عتاد الكمبيوتر الصلب - Yaser Chaaban, (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2020)
Nowadays, micro-programming of machines becomes more common. It is a technique used in several fields such as Computer Engineering. Here it is worth mentioning that micro-programming is employed throughout the design process. As well, designing the control unit of digital computers needs micro-programming, which is more complex than assembly languages. In this field, micro-programs can be written as sequences of micro-instructions. In this context, distinguished teaching of micro-programming of machines requires a suitable and carefully chosen Computer Simulation Tool (CST). This research designs a computer hardware project that introduces a special simulator achieving an easy-to-use microprogramming environment and a user-friendly simulation tool. This tool presents a visualization environment in order to display the execution behaviour of microprograms. It is a model/tool designed as a java program to ensure platform independence. This paper presents the Minimax simulator, which is used in the Minimax project. This project is a part of a hardware practical course. Therefore, it is a simulator for microprogramming and hardware simulation. As a result, this simulator facilitates the process of micro-programming significantly enabling students to understand easily how a computer works. Here, two formal measures and metrics were presented to assess the implemented program, the execution time and the program length. Other results of this study showed how self-organized group work and project management can be accomplished.
Keywords: محاكي; البرمجة المصغرة; لغة الآلة; محاكاة العتاد الصلب; مشروع عتاد صلب الحاسوب